Marine Characteristic Changes Associated with Typhoon Soulik Observed Using Wave and Underwater Gliders - Jong-Wu Hyeon; Dae-Hyeong Ji; Seom-Kyu Jung; Sung-Hyub Ko (Proceedings of Engineering and Technology Innovation, 2024)
To assess the impact of Typhoon Soulik on the marine environment, unmanned platforms, specifically wave and underwater gliders, are used for surveys in the East Sea. From August 20 to 30, 2018, the wave glider collected meteorological data, while the underwater glider conducts CTD measurements within the typhoon’s impact zone. The data are compared with marine buoy data from the Korea Meteorological Administration and forecast model outputs using RMSE and correlation coefficients to evaluate the characteristics of each data source. The unmanned platform effectively capture the marine environmental changes during the typhoon passage, and the forecast model results show relatively lower RMSE and correlation with the observed data. The study also determines the time required for conditions to revert to pre-typhoon states. This research demonstrates the potential of unmanned platform data for enhancing marine surveys and forecast model accuracy.